The Implementation of Blended Learning in English for Arts Education Program: A Case Study - Nindya Primandita Kristianingrum; Agus Widyantoro (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This study aims at exploring the blended learning implementation in English for Arts Education Program and reporting lessons learned from the practice. Some theories regarding blended learning adoption and English for Specific Purposes (ESP) were utilized as the theoretical framework. As this case study was conducted in the ESP course in the Arts Education study program of a private university in Yogyakarta, Indonesia, a qualitative case study research design was employed, resulting in an in- depth description of the overall implementation. The data were collected through in-class and online observations, a semi-structured interview, and a focus group discussion (FGD) conducted in two classes employing blended learning, 20 representative students recruited by purposive sampling technique, and the lecturer of the course. The results were analyzed descriptively using content analysis. Based on the analysis, some stages undergone by the lecturer were drawn as they are in line with blended learning adoption stages and framework. Thus, some lessons learned reveal concerns on flexibility and accessibility to technologies and learning sources, a balanced portion of collaborative and independent learning, Information Technology (IT) knowledge, and material clarification and immediate feedback that play significant roles to students’ skill improvement and effectiveness of a blended learning course. This study offers new insights for lecturers, institutions, and students planning to adopt this approach for the findings present consideration of elements required in developing a blended learning course.